Biochemical study for gold and silver nanoparticles on thyroid hormone levels in saliva of patients with chronic renal failure - Jassim, Abdulkadir Mohammed Noori; Al-Kazaz, Fatin Fadhel Mohammed (European Journal of Chemistry, 2013)
Noble metal nanoparticles were synthesized directly by pulsed laser ablation (Nd:YAG, λ=1064 nm) of gold and silver plates immersed in pure water. Concentrations of the nanoparticles were determined by atomic absorption spectroscopy measurement. Atomic force microscope and transmission electron microscope analysis were used to characterize the size and size distributions of the metals nanoparticles. The objective of this work is studying the effects of presence gold and silver nanoparticles on the levels of tri-iodothyronine hormone (T3) in saliva of patients with chronic renal failure their thyroid had disorder (hypothyroidism). Also the study characterized the binding between the anti-T3antibody with its antigen i.e., T3 in saliva patients in the presence affixed size concentration of nanoparticles to improve and modify a competitive ELISA method. It is found that both gold and silver nanoparticles demonstrated activation effect on the binding between anti-T3 antibody and antigen (T3) in the saliva of patients and these effects increased with increasing the concentrations and size for both nanoparticles (gold was more activation effect than silver). Optimization of experimental conditions for the binding in the saliva were: 40 μL and 20 μL of saliva (T3) in presence both silver and gold nanoparticle, respectively, pH = 7.4 of 0.2 M phosphate buffer was selected as the detection solution, the temperature of incubation was 22 °C while the incubation time were 30 min, 90 min for silver and gold nanoparticles, respectively.